2009
DOI: 10.1038/oby.2008.661
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Hepatic Steatosis in Zucker Diabetic Rats: Spontaneous Evolution and Effects of Metformin and Fenofibrate

Abstract: No specific treatment for nonalcoholic hepatic fatty liver disease has been defined. We followed the spontaneous evolution of liver steatosis and tested the therapeutic usefulness of metformin and fenofibrate in a model of steatosis, the Zucker diabetic fatty (ZDF) rat. ZDF and control rats were studied at 7, 14, and 21 weeks. After initial study at 7 weeks, ZDF rats received no treatment, metformin or fenofibrate until studies at 14 or 21 weeks. ZDF rats were obese, hypertriglyceridemic, insulin resistant at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 50 publications
2
26
0
Order By: Relevance
“…35 The central role of CPT-1 in the development of hepatic steatosis has also been shown both in vivo and in vitro: moderate overexpression 36 or induction of CPT-1 has been shown to improve diet-induced steatosis of the liver in different NASH models. 37,38 By contrast, a reduction of CPT-1 activity along with other mitochondrial defects, which preceded the development of steatosis and NASH, has been implicated as leading cause for disease development in the Otsuka Long-Evans Tokushima Fatty rat model of NASH. 39 In further support of a contribution of impaired mitochondrial b-oxidation to steatosis, inhibition of CPT-1 has been identified as a possible underlying mechanism in drug-induced steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…35 The central role of CPT-1 in the development of hepatic steatosis has also been shown both in vivo and in vitro: moderate overexpression 36 or induction of CPT-1 has been shown to improve diet-induced steatosis of the liver in different NASH models. 37,38 By contrast, a reduction of CPT-1 activity along with other mitochondrial defects, which preceded the development of steatosis and NASH, has been implicated as leading cause for disease development in the Otsuka Long-Evans Tokushima Fatty rat model of NASH. 39 In further support of a contribution of impaired mitochondrial b-oxidation to steatosis, inhibition of CPT-1 has been identified as a possible underlying mechanism in drug-induced steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previously reported features of ZDF rats also include raised plasma haemoglobin A 1c , impaired glucose tolerance, hyperinsulinaemia, hyperlipidaemia and moderate hypertension (Welch et al 2006;Pontes Andersen et al 2008;Forcheron et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Fatty acid oxidation assays were performed in fresh hepatic tissue preparations, using radiolabeled [1-14 C]palmitate (American Radiochemicals) as described previously (42). Briefly, the oxidation rate of [ 14 C]palmitate was measured by collecting and counting the 14 CO2 produced (representing complete fatty acid oxidation) and 14 C-labeled acid-soluble metabolites (representing incomplete fatty acid oxidation) that were collected within a trapping device and counted with a liquid scintillation counter. Palmitate oxidation experiments were performed in the presence (100 uM) or absence of etomoxir (a specific inhibitor of mitochondrial carnitine palmitoyl-CoA transferease-1 and entry into the mitochondria) to examine the relative contribution of mitochondrial (Ϫ etomoxir) and extramitochondrial organelles (ϩ etomoxir) in total fatty acid oxidation, as described previously (46).…”
Section: Methodsmentioning
confidence: 99%
“…Human studies have shown that continued metformin use helps sustain reductions in circulating serum alanine aminotransferase (ALT) levels in individuals at risk for developing type 2 diabetes (22) and with early liver disease (31), and these reductions may be due in part to metformin-induced reductions in body weight (22). Metformin also has been shown to improve liver TG content in some rodent models of diabetes and NAFLD (14,25). However, it is unknown whether the efficacy of treating NAFLD in the setting of type 2 diabetes may be enhanced if metformin was taken in combination with exercise.…”
mentioning
confidence: 99%